Pengaruh Budaya Religius terhadap Sikap Spiritual Peserta Didik SD Terpadu Ainul Ulum Pulung Ponorogo - Sugianto, Oga; Asfahani, Asfahani; Salahuddin, Marwan (BASICA, 2022)
Educational institutions have various kinds of religious cultures that are applied in their organizational systems. However, not all educational institutions have their own culture, which is a characteristic of these educational institutions. Spiritual attitudes are very appropriate to be implemented in the school environment, and this is because schools are a place for interaction between others, gathering with peers, and communication, so it becomes a very strategic place for fostering, directing, and preparing students to become religious figures. This study aims to determine religious culture, the formation of spiritual attitudes, and the influence of religious culture on the spiritual perspectives of students at SD Terpadu Ainul Ulum Pulung Ponorogo. This type of research is quantitative with questionnaires and documentation data collection procedures; the object of this research is SD Terpadu Ainul Ulum Pulung. The population of this research is the students of SD Terpadu Ainul Ulum, while the sample is 50% of the population, which is 45 students. Data related to religious culture and students' spiritual attitudes were analyzed correlational, while data associated with the influence of religious culture on spiritual attitudes were analyzed correlational using the Contingency Correlation formula. The results of data analysis: (1) The application of religious culture is good. This is known from the results of the study, which showed the highest percentage (73%), (2) students' spiritual attitudes were in a good category. This is known from the results of the study, which showed the highest percentage was 62.2%), (3) Based on the results of the analysis, it can be concluded that there is a significant influence between religious culture on the self-adjustment ability of SD Terpadu Ainul Pulung Ponorogo students.. Keywords: Religious culture; Learners, Spiritual Attitude Abstrak: Lembaga pendidikan memiliki berbagai macam budaya religius yang diterapkan didalam sistem organisasinya. Namun tidak semua lembaga pendidikan memiliki budaya tersendiri yang menjadi suatu ciri khas bagi lembaga pendidikan tersebut. Sikap spiritual sangat tepat diimplementasikan di lingkungan sekolah, hal ini disebabkan karena sekolah merupakan salah satu wadah untuk interkasi antar sesama, kumpul dengan sebaya, komunaksi, sehingga menjadi tempat yang sangat strategis dalam membina, mengarahkan dan mempersiapkan peserta didik menjadi sosok yang religius. Penelitian ini bertujuan untuk mengetahui budaya religius, pembentukan sikap spiritual, dan pengaruh budaya religius terhadap sikap spiritual peserta didik di SD Terpadu Ainul Ulum Pulung Ponorogo. Jenis penelitian ini kuantitatif dengan prosedur pengumpulan data kuesioner dan dokumentasi, objek penelitian ini yakni SD Terpadu Ainul Ulum Pulung. Populasi dari penelitian ini yakni selurus siswa siswi SD Terpadu Ainul Ulum, sedangkan sampelya yakni 50% dari populasi yaitu 45 siswa. Data yang terkait tentang buadaya religius dan sikap spiritual siswa dianalisis secara korelasional, sedangkan data terkait dengan pengaruh budaya religius terhadap perilaku sikap spiritual dianalisis secara korelasional dengan rumus Korelasi Kontingensi. Hasil analisis data: (1) Penerapan budaya religius sudah baik. Hal ini diketahui dari hasil penelitian yang menunjukkan prosentase tertinggi (73%), (2) Sikap Spiritual siswa termasuk kategori baik. Hal ini diketahui dari hasil penelitian yang menunjukkan prosentase tertinggi 62,2%), (3) Berdasarkan hasil analisis tersebut dapat disimpulkan bahwa terdapat pengaruh yang signifikan antara budaya religius terhadap kemampuan penyesuaian diri siswa SD Terpadu Ainul Pulung Ponorogo. Kata Kunci: Budaya religius; Peserta Didik, Sikap Spiritual